Selenoprotein A of the clostridial glycine reductase complex: purification and amino acid sequence of the selenocysteine-containing peptide. - Sliwkowski, M X (1988)
A selenium-containing protein, selenoprotein A, is an essential component of the clostridial glycine reductase complex. This enzyme complex catalyzes the reductive deamination of glycine, which is coupled to the esterification of orthophosphate resulting in the formation of ATP. Sequence information was obtained by automated Edman degradation of peptides generated by digesting carboxamidomethylated selenoprotein A with chymotrypsin or trypsin or with endoproteinase Arg-C followed by Staphylococcus aureus V8 protease. The sequence near the selenocysteine (Sec) residue is -Cys-Phe-Val-Sec-Thr-Ala-Ala-Gly-Ala-Met-Asp-Leu-Glu-Asn-Glu-Lys-. Selenium-containing peptides isolated from digests of carboxamidomethylated selenoprotein A with trypsin or endoproteinase Arg-C were found to be blocked at the amino terminus. The sequence of the selenocysteine-containing peptide from selenoprotein A shows no homology with those of two other selenoproteins, glutathione peroxidase and formate dehydrogenase.